Student Independence In Career Planning in 6 Padang Vocational High School - Rahmatul Marwani; Netrawati Netrawati (Jurnal Neo Konseling, 2020)
Independence is an attitude that is owned by someone to do everything themselves (independent), able to make their own decisions and account for their decisions in this case a person has freedom in acting and making decisions, as well as in terms of career planning. Students are able to be independent in career planning. But the reality found there are still some students who do not know the direction of their careers, go along with choosing a career as chosen by their peers, and do not understand their potential to choose a future career. This study aims describe the independence of behavior, and independence of assessment. This type of research is a type of descriptive research. The research population is  students of class XII of six public vocational in padang who were enrolled in the 2019/2020 academic year, amounting to 441 people. Samples were taken using a purposive sampling technique to obtain a total sample of 202 people. The study was conducted by administering the questionnaire instrument. Data were analyzed by percentage analysis. The research findings show the results: the independence of students in overall career planning is in the quite independent category, the independenceof students in career planning viewed from emotional independence is in the categoryof quite independent, the independence of students in career planning seen from the independence behavior is in the category of sufficient independence, and the independence of students in career planning seen from  the independence of assessment is in the category of quite independent.